PENGGUNAAN MEDIA FLASHCARD UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMULA - Widy Wardah Wahyuni; Ade Maftuh (Jurnal Evaluasi dan Pembelajaran, 2023)
This research was motivated by the lack of students' initial reading ability in class I SDN Cikembang Salopa. The purpose of this study was to describe the increase in students' initial reading skills in limb vocabulary material using flashcard learning media. The research method used was Classroom Action Research (PTK) with the research subject of first grade students at SDN Cikembang. Based on the results of research by applying flashcard learning media to improve students' reading skills on limb vocabulary material. This can be seen from the acquisition of the observation scores of students' initial reading ability on limb vocabulary material, in the first cycle it achieved a score of 69.02 in the good category, and in the second cycle it achieved a score of 80.92 in the very good category. So the increase from cycle I to cycle 2 is 28,57%. This instructional media is recommended for use in improving students' initial reading skills.